Effect of dietary inclusion of taurine on performance, carcass characteristics and muscle micro-measurements in broilers under cyclic heat stress - Abdul Hafeez; Wasim Akram; Asad Sultan; Yusuf Konca; Tugay Ayasan; Shabana Naz; Walikhan Shahzada; Rifat Ullah Khan (Italian Journal of Animal Science, 2021)
In the past, taurine was not considered essential in poultry diet; however, heavy reliance on plants derived feed ingredients and environmental stresses have compelled its application inevitable. Six hundred day old male broilers (Hubbard) were supplementation with taurine at the level of 0 (TAN0), 2.5 (TAN2.5), 5 (TAN5) and 7.5 g/kg (TAN7.5) in drinking water during heat stressed conditions for a period of 35 days. On overall basis, feed intake was not significantly (p>.05) different between the treatments. At the end of the experiment, weight gain was significantly (p<.05) higher in the treatment groups. On the overall basis, FCR was significantly (p<.01) lower in the treatment groups. Abdominal fat weight was significantly (p<.01) lower in TAN5 and TAN7.5 compared to the control group. On the slaughter age (35 days) muscle fibre diameter (MFD), muscle fibre cross sectional area (MFCSA), muscle fascicle diameter (MFASD) and muscle fascicle cross-sectional area were significantly (p<.05) higher in TAN7.5 compared to the control. The results indicated that growth performance was enhanced in taurine supplemented birds irrespective of the inclusion levels during the heat stress. Abdominal fat was significantly decreased in TAN5 and TAN7.5 levels; however, muscle histological features were significantly higher in all treatment groups.Highlights Heat stress (HS) adversely affect the performance of broilers. Taurine improved the performance of birds during HS. Taurine reduced the abdominal fat in HS broilers.